Colonoscopy in Patients With Postmyocardial Infarction Gastrointestinal Bleeding: A Nationwide Analysis. Issue 1 (January 2019) - Modi, Rohan M.; Li, Feng; Mumtaz, Khalid; Hinton, Alice; Lilly, Scott M.; Hussan, Hisham; Levine, Edward; Zhang, Cheng; Conwell, Darwin L.; Krishna, Somashekar G.; Stanich, Peter P.
Abstract : Goals: The goal of this study was to evaluate outcomes of colonoscopy in the setting of post myocardial infarction (MI) gastrointestinal bleeding (GIB) in a large population-based data set. Background: The literature to substantiate the proposed safety of colonoscopy following an acute MI is limited. Study: The Nationwide Inpatient Sample (2007 to 2013) was utilized to identify all adult patients (age, 18 y or above) hospitalized with a primary diagnosis of ST-elevation MI and receiving left heart catheterization (STEMI-C). The outcomes of patients with concomitant diagnosis of GIB receiving endoscopic intervention with esophagogastroduodenoscopy (EGD) or colonoscopy postcatheterization were compared with those who did not. Primary outcomes including mortality, length of stay, and hospital costs were evaluated with univariate and multivariate analysis. Results: There were 131, 752 patients with post-STEMI-C GIB (5.35% of all STEMI-C patients) and same admission colonoscopy was performed in 1599 patients (1.21%). Although the prevalence of post-STEMI-C GIB increased from 4.27% in 2007 to 5.87% in 2013 ( P <0.001), patients receiving colonoscopy decreased from 1.42% to 1.09% ( P <0.001) over the course of the study period. Multivariate analysis revealed that patients receiving no endoscopic intervention [odds ratio, 3.61; 95% confidence interval: 1.57, 8.31] or EGD alone (OR, 2.70; 95% confidence interval: 1.12, 6.49) have higher mortality compared with those receiving colonoscopy. Conclusions: Same admission colonoscopy performed for post-STEMI-C GIB was associated with lower mortality. However, despite increased incidence of GIB in these patients during the study period, a lower percentage of patients received colonoscopy. These results suggest that colonoscopy is safe but underutilized in this setting. Abstract : Supplemental Digital Content is available in the text.